Analysis Of The Influence Of Store Environment, Product Innovation And Service Quality On Consumer Purchasing Decisions Of Coffee Shop Ming Kopi Medan - Victor Victor; August Halomoan Siregar; Jesslyn Toffany (International Journal of Economics and Management Research, 2024)
This research aims to find out what influence the store environment, product innovation and service quality have on consumer purchasing decisions at the Ming Kopi Medan Coffee shop. The type of research used is a quantitative descriptive research method, sampling was carried out using snowball sampling techniques and using the Cochran formula because the population size is unknown. The number of samples taken was 97 consumers and data was collected through questionnaires distributed directly to consumers. To assess respondents' responses, the author uses a Likert scale which uses several question items to measure individual behavior by responding to 5 choice points for each question item. Analysis was carried out using descriptive statistics, data quality tests, classical assumption tests, multiple linear regression analysis, hypothesis testing, and coefficient of determination using the SPSS version 25 program (IBM SPSS Statistics 25). The research results show that simultaneously, the calculated F value (20.555) is greater than the F table value (2.70) with a significance level of 0.000 < 0.05 which shows that H4 is accepted which shows a positive and significant influence from store environment, product innovation and service quality on purchasing decisions. Partially, hypothesis testing reveals that store environment (t = 3.934), product innovation (t = 2.227) and service quality (t = 2.171) each have a positive and significant impact on purchasing decisions because they are greater than the t value table (1.985), with the significance level for each variable being 0.000; 0.028; and 0.001. Therefore, the conclusion of this research is that store environment, product innovation and service quality, both partially and simultaneously, have a significant influence on consumer purchasing decisions at the Ming Kopi Medan coffee shop.